Teaching around the 4MAT cycle : designing instruction for diverse learners with diverse learning styles - McCarthy, Bernice. 4 0 16; 1961- McCarthy, Dennis; 5 (Thousand Oaks, CA. : Corwin Press, 2006)
Describes and explains how to apply the 4MAT learning cycle teaching method in the classroom.
Learning styles -- A cycle of learning -- Teaching around the cycle -- The brain-mind learning system -- Overlaying right- and left-mode to complete the 4MAT cycle -- Teaching from concepts -- The 4MAT design overlay (lesson planning).
Includes bibliographical references (page 95-97) and index.
Reference and Research Book News, November 2006;Reference and Research Book News
Professional;Professional
Keywords: 2 -- 0; 6; 4MAT system.;Learning.;Left and right (Psychology);Learning, Psychology of. -- 20; 20; 2